EARLY CORE FORMATION IN ASTEROIDS AND LATE ACCRETION OF CHONDRITE PARENT BODIES: EVIDENCE FROM 182HF-182W IN CAIS, METAL-RICH CHONDRITES, AND IRON METEORITES - Kleine T.; Mezger K.; Palme H.; Scherer E.; M?nker C. (My University, 2005)
The 182Hf-182W isotopic systematics of Ca-Al-rich inclusions (CAIs), metal-rich chondrites, and iron meteorites were investigated to constrain the relative timing of accretion of their parent asteroids. A regression of the Hf-W data for two bulk CAIs, various fragments of a single CAI, and carbonaceous chondrites constrains the 182Hf/180Hf and εW at the time of CAI formation to (1.07 ± 0.10) × 10−4 and −3.47 ± 0.20, respectively. All magmatic iron meteorites examined here have initial εW values that are similar to or slightly lower than the initial value of CAIs. These low εW values may in part reflect 182W-burnout caused by the prolonged cosmic ray exposure of iron meteorites, but this effect is estimated to be less than ∼0.3 ε units for an exposure age of 600 Ma. The W isotope data, after correction for cosmic ray induced effects, indicate that core formation in the parent asteroids of the magmatic iron meteorites occurred less than ∼1.5 Myr after formation of CAIs. The nonmagmatic IAB-IIICD irons and the metal-rich CB chondrites have more radiogenic W isotope compositions, indicating formation several Myr after the oldest metal cores had segregated in some asteroids.